2000
DOI: 10.1097/00006254-200005000-00015
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Controlled Trial Comparing Transvaginal Ultrasound, Outpatient Hysteroscopy and Endometrial Biopsy With Inpatient Hysteroscopy and Curettage

Abstract: Objective To compare the use of outpatient and inpatient procedures in the investigation of abnormal Design A randomised controlled trial.Setting Two university teaching hospitals.Participants Four hundred women with abnormal uterine bleeding (postmenopausal bleeding, menorrhagia, intermenstrual bleeding, postcoital bleeding, or irregular periods) above the age of 35 years, between June 1993 and January 1995.1. Incidence of detection of abnormal pathology by vaginal ultrasound, outpatient hysteroscopy and endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 0 publications
1
46
2
1
Order By: Relevance
“…Dilatation and curettage under general anesthesia used to be considered the gold standard. [3] However, the predictive value of hysteroscopy and endometrial sampling on an outpatient basis for both benign and neoplastic pathology has been well documented [3][4][5] and is now considered the gold standard. Generally, all patients attending our clinic have TVS done, and this has shown 100% accuracy in detecting endometrial cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Dilatation and curettage under general anesthesia used to be considered the gold standard. [3] However, the predictive value of hysteroscopy and endometrial sampling on an outpatient basis for both benign and neoplastic pathology has been well documented [3][4][5] and is now considered the gold standard. Generally, all patients attending our clinic have TVS done, and this has shown 100% accuracy in detecting endometrial cancers.…”
Section: Discussionmentioning
confidence: 99%
“…13,27 Diagnostic hysteroscopy allows direct visualization and biopsy of diffuse or focal abnormalities of the endometrium. 10 Direct visualization of the uterine cavity is a simple and effective method for investigating endometrial and even endocervical pathologies. 20 Hysteroscopy showed great efficiency in the diagnosis of focal abnormalities of the endometrium, which are hardly recognized by ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…9,12,16/18 Different cutoff levels for endometrial thickness have been used, resulting in varying degrees of reliability for detecting endometrial disease. 9,10,12,18 If the endometrium is 4 mm or less as measured by TVS, endometrial abnormality can be excluded with a high probability. 1,8,14,15 It has also been shown that TVS can accurately identify abnormal structures within the endometrial cavity and the myometrium.…”
mentioning
confidence: 99%
“…According to previous reports hysteroscopy with endometrial biopsy is mandatory in postmenopausal women with AUB and can be satisfactorily used as a second-line investigation to find the reasons for bleeding (59,60).…”
Section: Discussionmentioning
confidence: 99%